Mobile learning in medicine: an evaluation of attitudes and behaviours of medical students - Thomas J. G. Chase; Adam Julius; Joht Singh Chandan; Emily Powell; Charles S. Hall; Benedict Lyle Phillips; Ryan Burnett; Deborah Gill; Bimbi Fernando (BMC Medical Education, 2018)
Abstract Background Mobile learning (mLearning) devices (such as tablets and smartphones) are increasingly part of the clinical environment but there is a limited and somewhat conflicting literature regarding the impact of such devices in the clinical learning environment. This study aims to: assess the impact of mLearning devices in the clinical learning environment on medical students’ studying habits, attitudes towards mobile device supported learning; and the perceived reaction of clinicians and patients to the use of these devices as part of learning in the clinical setting. Methods Over three consecutive academic years, 18 cohorts of medical students (total n = 275) on a six-week rotation at a large teaching hospital in London were supplied with mLearning devices (iPad mini) to support their placement-based learning. Feedback on their experiences and perceptions was collected via pre- and post-use questionnaires. Results The results suggest mLearning devices have a positive effect on the students’ perceived efficiency of working, while experience of usage not only confirmed pre-existing positive opinions about devices but also disputed some expected limitations associated with mLearning devices in the clinical workplace. Students were more likely to use devices in ‘down-time’ than as part of their clinical learning. As anticipated, both by users and from the literature, universal internet access was a major limitation to device use. The results were inconclusive about the student preference for device provision versus supporting a pre-owned device. Conclusion M-learning devices can have a positive impact on the learning experiences medical students during their clinical attachments. The results supported the feasibility of providing mLearning devices to support learning in the clinical environment. However, universal internet is a fundamental limitation to optimal device utilisation.